Implementación de un sistema web de matriculación en línea y gestión de calificaciones para la Unidad Educactiva Particular “García” en el cantón Guaranda, año 2019. - Moyano Velasco, Mayra Alexandra (2019)
This research project aims to Implement a Web System for Online Enrollment and Management of qualifications for the Educational Unit "García" in the canton Guaranda, year 2019. Through different research methods, techniques and instruments such as observation, surveys and interviews, it was possible to determine the enrollment processes and qualifications and requirements of the "García" Educational Unit, for its automation and to meet the objectives set forth in this research. To implement the automated system in the "García" Educational Unit, software engineering and specifically the RAD (Rapid Application Development) methodology were used, for the development we worked with programming languages such as: HTML, JavaScript PHP5, AJAX, Bootstrap, CSS and as a PostgreSQL database manager. The following hypothesis was raised: The Implementation of an Online Web System of the "García" Educational Unit will reduce response times in the enrollment and qualification management processes, which was demonstrated by applying the Chi square, which will speed up the processes of enrollment and preparation of report cards, teachers, students who are requested.